Evaluating Employee Motivation in Expanding Adult Primary Services: A Grant-Funded Project - Smith, Devin (My University, 2024)
Many parts of North Carolina are considered rural, especially in Eastern North Carolina. In these rural areas access to healthcare continues to be an ongoing concern. Employee motivation was evaluated as a local health department utilized grant-funding to help expand clinical services. The RE-AIM framework was utilized by completing Bono’s Six Thinking Hats exercise, a pre-and post-expansion survey as well as continued education on the topic of employee motivation and how it relates to grant funding. Employee motivation was evaluated, and progress was made towards the greater goal of the grant-funded project. It was found that post-expansion of services, after all interventions of the project, all results in the survey were improved regarding employee motivation, with the most significant being in improved clear communication. Through these findings, employee motivation is an excellent factor in evaluating departmental change. It is also important to consider grant funding and its success as a factor to departmental change.
Keywords: employee motivation, change, adult primary care services, grant funding